PROGRAM APPLICATION to play WITH AUDIO AND VIDEO USING DELPHI 6 ActiveX controls WINDOWS MEDIA PLAYER - Tony Sugiarto 30401341 (Jurnal Sistem Informasi, 2005)
Along with the development of computer technology so rapidly, computers today are not only used as a working tool but it can also be used as a medium for entertainment, like to listen to music or watching videos, so you no longer need these media. In the play audio and video via computer media, there are two things that must be considered a computer that is used to develop software programs and have facilities elements combine audio and video in one software. Software that can be used to vary considerably from the simple to the complex which has a high level. Each level in the variation affects the level of the software user satisfaction. Many of the actual products that can be selected to play audio and video, but the distinction between programming language with Sotware authoring.